Testing distance characteristics and reference values for ice-hockey straight sprint speed and acceleration. A systematic review and meta-analyses - Stastny, Petr; Musalek, Martin; Roczniok, Robert; Cleather, Daniel; Novak, Dominik; Vagner, Michal (Biology of Sport, 2023)
Ice-hockey requires high acceleration and speed sprint abilities, but it is unclear what the distance characteristic is for measuring these capabilities. Therefore, this systematic meta-analysis aims to summarize the sprint reference values for different sprint distances and suggest the appropriate use of ice-hockey straight sprint testing protocols. A total of 60 studies with a pooled sample of 2254 males and 398 females aged 11-37 years were included. However, the pooled data for women was not large enough to permit statistical analysis. The sprint distance used for measuring the reported acceleration and speed was between 4-48 m. Increased test distance was positively associated with increased speed (r = 0.70) and negatively with average acceleration (r = -0.87). Forward skating sprint speed increases with the measured distance up to 26 m and do not differ much from longer distance tests, while acceleration decreases with a drop below 3 m/s at distances 15 m and longer. The highest acceleration (5.89 m/s2 peak, 3.31 m/s2 average) was achieved in the shortest distances up to 7 m which significantly differs from 8-14 m tests. The highest speed (8.1 m/s peak, 6.76 m/s average) has been recorded between 26-39 m; therefore, distances over 39 m are not necessary to achieve maximum speed. Considering match demands and most reported test distances, 6.1 m is the recommended distance for peak acceleration and 30 m for peak speed. The sprint time, acceleration, and speed of each individual and the number of skating strides should be reported in future studies.